Long-term Risk of Colorectal Cancer and Related Death After Adenoma Removal in a Large, Community-based Population - Lee, Jeffrey K; Jensen, Christopher D; Levin, Theodore R; Doubeni, Chyke A; Zauber, Ann G; Chubak, Jessica; Kamineni, Aruna S; Schottinger, Joanne E; Ghai, Nirupa R; Udaltsova, Natalia; Zhao, Wei K; Fireman, Bruce H; et al. (Gastroenterology (New York, N.Y. 1943), 2020)
The long-term risks of colorectal cancer (CRC) and CRC-related death following adenoma removal are uncertain. Data are needed to inform evidence-based surveillance guidelines, which vary in follow-up recommendations for some polyp types. Using data from a large, community-based integrated health care setting, we examined the risks of CRC and related death by baseline colonoscopy adenoma findings. Participants at 21 medical centers underwent baseline colonoscopies from 2004 through 2010; findings were categorized as no-adenoma, low-risk adenoma, or high-risk adenoma. Participants were followed until the earliest of CRC diagnosis, death, health plan disenrollment, or December 31, 2017. Risks of CRC and related deaths among the high- and low-risk adenoma groups were compared with the no-adenoma group using Cox regression adjusting for confounders. Among 186,046 patients, 64,422 met eligibility criteria (54.3% female; mean age, 61.6 ± 7.1 years; median follow-up time, 8.1 years from the baseline colonoscopy). Compared with the no-adenoma group (45,881 patients), the high-risk adenoma group (7563 patients) had a higher risk of CRC (hazard ratio [HR] 2.61; 95% confidence interval [CI] 1.87-3.63) and related death (HR 3.94; 95% CI 1.90-6.56), whereas the low-risk adenoma group (10,978 patients) did not have a significant increase in risk of CRC (HR 1.29; 95% CI 0.89-1.88) or related death (HR 0.65; 95% CI 0.19-2.18). With up to 14 years of follow-up, high-risk adenomas were associated with an increased risk of CRC and related death, supporting early colonoscopy surveillance. Low-risk adenomas were not associated with a significantly increased risk of CRC or related deaths. These results can inform current surveillance guidelines for high- and low-risk adenomas.